TRIANGULAR DESIRE: THE GAY GAZE IN LORCA’S “LA CASADA INFIEL” - Kramer, Max (ConSecuencias, 2019)
This essay looks at the queer mediation in Federico García Lorca’s “La casada infiel.” The poem has mostly been read from a feminist point of view, with the assumption of a heterosexual narrative, and construed as a mockery of the macho protagonist’s performance. In such readings, the straight, feminist readers, far from being enthralled by the speaker’s hegemonic male behavior, are meant to be repulsed by this deeply misogynistic man. The chief point of this essay is that “La casada infiel,” an overtly heterosexual poem which reads like a “locker room scene” and invokes the specter of male ownership in the form of a husband, in fact masks a homosexual perspective that is carefully attuned to the cultural expectations of the time. The poem actually serves as code for homosexual desire. The Andalusian poet took advantage of the ambiguity that was inherent in a certain cultural setting and literary form—that is, the Romani milieu and the Spanish ballad (romance)—in order to detach himself publicly from the queer content of the poem while still representing it. My essay shows that a poem that is perfectly integrated into the heteronormative canon can also offer a queer perspective. Resumen Este ensayo analiza la mediación queer en “La casada infiel” de Federico García Lorca. El poema se ha estudiado principalmente desde un punto de vista feminista, con la suposición de una narrativa heterosexual, e interpretado como una burla de la actuación del protagonista machista. En tales lecturas, se supone que el lector/la lectora heterosexual, feminista, lejos de quedarse cautivado/cautivada por la conducta hegemónica masculina del hablante lírico, siente repulsión por este hombre profundamente misógino. El punto principal de este ensayo es que “La casada infiel”, poema abiertamente heterosexual que se lee como una “escena de vestuario” y que invoca el espectro de la propiedad masculina en forma de esposo, de hecho enmascara una perspectiva homosexual que es puesta cuidadosamente en sintonía con las expectativas culturales de la época. En realidad, el poema sirve como código para el deseo homosexual. El poeta andaluz aprovechó la ambigüedad inherente a un determinado escenario cultural y a una cierta forma literaria, es decir, el entorno de los romaníes y el romance español, para distanciarse públicamente del contenido queer del poema mientras aún lo representaba. Mi ensayo muestra que un poema que está perfectamente integrado en el canon heteronormativo también puede ofrecer una perspectiva altersexual.